Comparative analysis of the efficiency of various energy storages - Zulfugarov, Bakir; Hasanov, Arif; Hashimov, Elshan (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2023)
The use of renewable energy creates the need to solve the problem of its discontinuity. Previous experience has shown that energy storage devices are best suited for this. They can be attributed to new technologies, since the operation of some energy storage devices is based on the latest achievements of modern science and technology. Energy storages is now at the beginning of its development, as renewable energy is still used to a limited extent. But which of the ubiquitous different types of energy storages is most likely to be the most efficient for the future industrial energy supply? The aim of the research was to obtain an answer to the above question. For this, seven types of energy storages, the use of which is spreading in the world, are analyzed in a comparative manner in terms of the most important parameters. The comparison was made using mathematical methods of data analysis, based on data collected from the relevant literature, and allows a fairly objective answer to the question under study.